TURKISH ADAPTATION STUDY OF CHILDRENS PERCEPTIONS OF THEIR PLAY (CPTP) SCALE - İhsan ÜNLÜ (Fırat University, 2019)
One of the biggest problems of educational scientists who reflecting the play into the classroom environment is that they can’t evaluate the children’s play from the point of their view. This is not just about the educators, but also about everyone (Family, friend, researcher) who is curious to the point of view children’s about the play. Especially how children perceive their own plays will provide important facilities for teachers who will use the play as an educational tool. It can be said that it is important to detect children's perceptions of their play, given the research that shows, childrens are defined play qualitatively in a different way than adults. In this context, it is important to form a scale form that will help children express their thoughts about the play. In this context, it is important to establish a scale that will help children express their thoughts about the play. In the research, it was aimed to perform the adaptation study to the Turkish culture of "Childrens Perceptions of Their Play" (CPTP) scale, developed by Barnett (2013). The adaptation study of the scale was performed with the confirmatory factor analysis process. The research was conducted with 315 students. The psychometric properties of the scale were tested by structural validity and structural reliability in order to check the appropriateness of the process of developing the original form of the scale. As a result of the adaptation studies carried out in our research sample, it was observed that there is an 11-point structure consisting of 4 dimensions